Sport and exercise recommendations for pregnant athletes: a systematic scoping review - Jörg Spörri; Johannes Scherr; Nora Wieloch; Anneke Klostermann; Nina Kimmich (BMJ Open Sport & Exercise Medicine, 2022)
Objectives To analyse the available evidence and identify gaps in current knowledge regarding physical activity volume and intensity and their effects on pregnancy outcomes in female athletes.Design Scoping review.Data sources A structured literature search of three electronic databases (Embase, PubMed and Web of Science) was conducted on 25 February 2022, and a rerun search was conducted on 8 September 2022.Eligibility criteria Studies were eligible if they contained information on the relevant population (ie, elite or competitive amateur female athletes), intervention/exposure (ie, minimum of 10 hours of sport per week) and fetal and maternal outcomes. Eligible comparators included female recreational athletes and pregnant non-exercisers.Risk of bias The risk of bias was evaluated with the National Institutes of Health (National Heart, Lung and Blood Institute) quality assessment tool.Results The results revealed a discrepancy between the number of original research papers and the number of reviews and recommendations derived from them. The identified studies focused primarily on pregnant recreational athletes. Sixteen clinical studies met the inclusion criteria. No adverse effects on maternal or fetal outcomes were reported. Only during performance tests involving acute intensive exercise with the mother exercising at more than 90% of her maximal heart rate did some fetuses experience decelerations in heart rate.Summary/conclusion A lack of high-quality studies and direct evidence on pregnant elite and competitive amateur female athletes is evident. Further prospective observational cohort studies are needed using new monitoring methods (eg, non-invasive, wireless monitoring systems) aiming to gain a broader understanding of the stress tolerance of pregnant athletes and fetuses during exercise. Following that, interventional studies with stress tests in laboratory settings should be conducted. Therefore, technology plays a decisive role in gaining new knowledge and providing evidence-based recommendations on this topic.PROSPERO registration number CRD42022309541.